Competition Law and Patent Protection in Japan: a Half-Century of Progress, a New Millennium of Challenges - Harris Jr., H. Stephen (Columbia Journal of Asian Law, 2003)
Japan, the United States and the European Union have made significant strides in building and harmonizing advanced competition’ and intellectual property laws and enforcement systems. The laws and policies of these jurisdictions reflect recognition of the fact that innovation and competition are the twin engines of progress. Despite progress over the past four decades, important differences remain. Some can be attributed simply to the imperfect and episodic way in which law develops. Some reflect deeply held views steeped in history and culture. Still others appear on occasion to be either engineered or invoked for political or protectionist purposes. Accusations and suspicions of exclusionary application of intellectual property and competition law and of protectionist trade policies by both sides2 have strained the relationship between Japan and the United States, especially in the late 1980’s and 1990’s.